2002
DOI: 10.1179/027249302125002029
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for neurological evaluation of infants in resource-poor settings

Abstract: Research assessing the neurological development of infants in developing countries is scanty as no suitable standardised tests are available for field-use in constrained circumstances. We describe the development and application of two simple assessments. Firstly, we aimed to develop a test suitable for assessing acute neurological disturbances caused by such diverse effects as infections, drugs or toxins. This test (Shoklo Neurological Test) is aimed at infants between 9 and 36 months. The second test (Shoklo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…The neurological assessment included evaluation of tonus, coordination, the status of consciousness, the emotional status and the social orientation [15]. In accordance with the presented data, this study showed no deterioration or deficits in coordination and tonus due to mefloquine-artesunate therapy, the other parameters showed no deterioration either, but were not directly comparable to items in our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The neurological assessment included evaluation of tonus, coordination, the status of consciousness, the emotional status and the social orientation [15]. In accordance with the presented data, this study showed no deterioration or deficits in coordination and tonus due to mefloquine-artesunate therapy, the other parameters showed no deterioration either, but were not directly comparable to items in our study.…”
Section: Discussionsupporting
confidence: 81%
“…This study was conducted from 1994 to 1997 in ninety-eight Asian children and used a specified neurological assessment for children (Shoklo Neurological Test and Shoklo Developmental Test [15]). Repeated assessments in children aged three months to five years were conducted until day 28 after first intake of mefloquine-artesunate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The infant neurodevelopment will be assessed using the Shoklo Developmental Test at 3, 6, and 12 months [14]. Scoring will be based on a pass/fail system for each item of the test; the global score of the test will be obtained by adding up all the passed scores of the following categories; eye-hand coordination, gross motor, social and speech development.…”
Section: Methodsmentioning
confidence: 99%
“…The development of infants was assessed by the investigators either through a general assessment (e.g. smiling, lifting head, sitting unsupported, standing without assistance, crawling) or the Shoklo neurodevelopment assessment [17], or both.…”
Section: Methodsmentioning
confidence: 99%